Impact of range shifter material on proton pencil beam spot characteristics. Issue 3 (25th February 2015) - Shen, Jiajian; Liu, Wei; Anand, Aman; Stoker, Joshua B.; Ding, Xiaoning; Fatyga, Mirek; Herman, Michael G.; Bues, Martin
Abstract : Purpose: To quantitatively investigate the effect of range shifter materials on single‐spot characteristics of a proton pencil beam. Methods: An analytic approximation for multiple Coulomb scattering ("differential Moliere" formula) was adopted to calculate spot sizes of proton spot scanning beams impinging on a range shifter. The calculations cover a range of delivery parameters: six range shifter materials (acrylonitrile butadiene styrene, Lexan, Lucite, polyethylene, polystyrene, and wax) and water as reference material, proton beam energies ranging from 75 to 200 MeV, range shifter thicknesses of 4.5 and 7.0 g/cm 2, and range shifter positions from 5 to 50 cm. The analytic method was validated by comparing calculation results with the measurements reported in the literature. Results: Relative to a water‐equivalent reference, the spot size distal to a wax or polyethylene range shifter is 15% smaller, while the spot size distal to a range shifter made of Lexan or Lucite is about 6% smaller. The relative spot size variations are nearly independent of beam energy and range shifter thickness and decrease with smaller air gaps. Conclusions: Among the six material investigated, wax and polyethylene are desirable range shifter materials when the spot size is kept small. Lexan and Lucite are the desirable range shifter materials when the scattering power is kept similar to water.